E-BEKAL AS CASHLESS PAYMENT IN IMPROVING THE QUALITY OF INSTRUCTIONAL SERVICES - Hidayatullah, Mohammad Alief; Rizal, Sofian Syaiful; Anggraini, Widya (Managere: Indonesian Journal of Educational Management, 2022)
This study analyzes E-Bekal as a cashless payment to improve service quality at the Nurul Jadid Islamic Boarding School. This research uses a qualitative approach with a case study type carried out through observation, interviews, and documentation. Data analysis starts with data presentation, data reduction, and conclusions. The results showed that improving the quality of services through E-Bekal was carried out through providing good facilities, socializing and promoting the system for using E-Bekal, providing E-Bekal cards to students, and providing consulting services, as well as providing cell phones that had an encryption network. With these services, it can help and provide service satisfaction for students.